Catching up with the Joneses and Borrowing Constraints: An Agent-based Analysis of Household Debt - Nadja König; Ingrid Größl (Hamburg University, Department Socioeconomics, 2014)
We study an Agent-based model of household-bank relationships where households borrow for the purpose of consumption. Desired consumption is driven by households disposable income as well as a social norm of consumption. If households care about their relative position in the economy (i.e. want to catch up with the Joneses), they are willing to take a loan. We conduct several computational experiments, where the absence of the social consumption norm (Joneses effect) functions as control treatment. Varying the strength of the social orientation and prevailing credit constraints, we find that the time path of macroeconomic time series is largely affected by the Joneses effect, while credit constraints determine their volatility. More precisely, we find that a strong Joneses effect has severe consequences for GDP growth and that borrowing constraints can reduce macroeconomic volatility. Since by assumption high-income and low-income households react equally sensitive to the Joneses effect, income distribution is the decisive variable for households social development. That said, access to credit exposes already poor households to find themselves caught in a poverty trap.
Keywords: D53; E21; 330; Household; Finance; and; Consumption; Credit; constraints; Agent-based; Model; Computational; Simulation